GH Overexpression Alters Spermatic Cells MicroRNAome Profile in Transgenic Zebrafish - Domingues, William B. (2021)
Overexpression of growth hormone (GH) in gh-transgenic zebrafish of a highly studied lineage F0104 has earlier been reported to cause increased muscle growth. In addition to this, GH affects a broad range of cellular processes in transgenic fish, such as morphology, physiology, and behavior. Reports show changes such as decreased sperm quality and reduced reproductive performance in transgenic males. It is hypothesized that microRNAs are directly involved in the regulation of fertility potential during spermatogenesis. The primary aim of our study was to verify whether gh overexpression disturbs the sperm miRNA profile and influences the sperm quality in transgenic zebrafish. We report a significant increase in body weight of gh-transgenic males along with associated reduced sperm motility and other kinetic parameters in comparison to the non-transgenic group. MicroRNA transcriptome sequencing of gh-transgenic zebrafish sperms revealed expressions of 186 miRNAs, among which six miRNA were up-regulated (miR-146b, miR-200a-5p, miR-146a, miR-726, miR-184, and miR-738) and sixteen were down-regulated (miR-19d-3p, miR-126a-5p, miR-126b-5p, miR-22a-5p, miR-16c-5p, miR-20a-5p, miR-126b-3p, miR-107a-3p, miR-93, miR-2189, miR-202–5p, miR-221–3p, miR-125a, miR-125b-5p, miR-126a-3p, and miR-30c-5p) in comparison to non-transgenic zebrafish. Some of the dysregulated miRNAs were previously reported to be related to abnormalities in sperm quality and reduced reproduction ability in other species. In this study, an average of 134 differentially expressed miRNAs-targeted genes were predicted using the in silico approach. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis demonstrated that the genes of affected pathways were primarily related to spermatogenesis, sperm motility, and cell apoptosis. Our results suggested that excess GH caused a detrimental effect on sperm microRNAome, consequently reducing the sperm quality and reproductive potential of zebrafish males.